Psikolojik Sermayenin İş Tatmini, Örgütsel Bağlılık ve Sinizm Üzerindeki Etkisi - Şen, Cem; Mert, İbrahim Sani (Muş Alparslan Üniversitesi, 2019)
Psychological capital has recently been a highly discussed variable inbusiness literature. The number of studies that has examined the effects ofpsychological capital on the organizational outcome variables has been increasedin the native and international literature. In this study, the effect ofpsychological capital on job satisfaction, organizational commitment andcynicism is examined. In this study which is a field research usingquantitative research design, the data is obtained from a total of 295participants who work in three different companies in the defense industry.According to the findings obtained from the research, psychological capital hasa meaningful effect on the study’s dependent variables which are jobsatisfaction, organizational commitment and cynicism.

Psikolojiksermaye son zamanlarda işletme yazınında üzerinde oldukça durulan bir değişkenolmuştur. Yerli ve uluslararası yazında psikolojik sermayenin örgütsel sonuçdeğişkenleri ile olan etkileri inceleyen çalışmaların sayısı artmıştır. Yapılanbu çalışmada, psikolojik sermayenin iş tatmini, örgütsel bağlılık ve sinizmüzerindeki etkisi incelenmiştir. Yapılan araştırma nicel araştırma desenikullanan, kesitsel bir alan araştırması olup, araştırma kapsamındaki verilersavunma sektöründe faaliyet gösteren üç farklı şirkette çalışan toplam 295katılımcıdan elde edilmiştir. Araştırmadan elde edilen bulgulara görepsikolojik sermaye, araştırmanın bağımlı değişkenleri olan iş tatmini, örgütselbağlılık ve sinizmi anlamlı olarak yordamaktadır.
The Effects of Psychological Capital on Job Satisfaction, Organizational Commitment and Cynicism
anemon
Keywords: Psychological Capital; Job Satisfaction; Organizational Commitment; Cynicism; Psikolojik Sermaye; İş Tatmini; Örgütsel Bağlılık; Sinizm